Prevalence of Gunshot Injuries Seen in Robbery Cases in Karachi and their Characteristic Features - Gulzar Ali, Ramlah Naz, Mehreen Fatima, Zubair Ahmed Tirmizi, Rafay Ahmed, Raheela Irshad, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the prevalence of gunshot injuries seen in robbery cases at different locations in Karachi and their characteristic features. Methodology: This retrospective observational study was conducted from January to December 2022 at the Office of the Police Surgeons in Karachi and comprised 63 gunshot cases. . Information related to the physical and internal examination of the cases was included. Death features like the presence of rigour mortis, post-mortem lividity, and bleeding status were also included. Results: The mean age was 35.30 ± 14.15, and 95.2% were males. Most of the cases were reported in Ittehad Town (20.6%), with 92.1% of participants having blood stains on their clothes. Around 88.9% had an average physique. Almost 84.1% were developing rigour mortis, 61.9% had post-mortem lividity and 87.3% had identifiable features. Exactly 50.8% of cases were not oozing blood from any wound or site. Internal examination was performed in 46% of the cases. Of which, 19% of participants still had the bullet inside their bodies. It was found that 57.1% of participants instantly died after the gunshot, while 34.9% died within a few minutes, respectively. Most of the participants received gunshots on their chests (n=35), and most of the participants received 2 to 4 bullets at a time (n=67). Conclusion: The high prevalence rate of gunshot injuries during robbery in Karachi. Higher authorities should strictly follow up on the increased number of casualties, and law and enforcement policies should be strictly followed to avoid further such cases. Keywords: Prevalence, Gunshot injuries, Robbery, Characteristic features